Keep them safe Outcomes Evaluation: KTS Indicators Final Report - Cassells, R.; Duncan, Alan; Eastman, C.; Gao, X.; Katz, I.; Keegan, M.; Mavisakalyan, Astghik; Shlonsky, A.; Smyth, C.; Valentine, K. (-, 2014)
This report provides a final analysis of a range of indicators of wellbeing of children and young people in New South Wales, in particular vulnerable children targeted by the KTS reforms. It is a companion report to the Final Report of the Keep Them Safe Outcomes Evaluation. One of the key aims of the evaluation is to examine the progress of the outcome indicators and whether or not targets have been met or positive changes have been achieved. Specifically, we examine the path to achieve the target and its variations at different time points and throughout different regions of NSW. Therefore, the first step is to compare the initial condition (ideally before substantial KTS investment) with a target or threshold line going forward.